STOCK QUOTES FOR US TECHNOLOGY COMPANIES AS A TOOL FOR SELECTING POTENTIAL AREAS FOR STARTUP IMPLEMENTATION (Multidisciplinary Journal of Science and Technology, 2024)
Increasingly, economic research is paying attention to the technological development of various economic entities. In this case, special attention is paid to the implementation of some business ideas based on startups. This attention to certain areas of economic research is based both on their importance from the point of view of economic development, and on the possibility of introducing innovative solutions in the shortest possible time. The main problem in this aspect is attracting a sufficient amount of financial resources in the shortest possible time. Based on this, the paper examines the dynamics of quotes for shares of technology companies. To solve the problem, the absolute values of such quotes were considered and the corresponding statistical analysis was carried out. As a result, the potential time periods for entering the corresponding segment of the stock market were substantiated.